Exon 20 YVMA insertion is associated with high incidence of brain metastasis and inferior outcome of chemotherapy in advanced non-small cell lung cancer patients with HER2 kinase domain mutations - Shuo Yang; Yan Wang; Chao Zhao; Xuefei Li; Qian Liu; Shiqi Mao; Yiwei Liu; Xiaofei Yu; Wanying Wang; Qinrun Tian; Yingying Pan; Anwen Xiong; et al. (2021)
Chemotherapy remains the standard care for HER2 mutated advanced non-small cell lung cancer (NSCLC) even though several targeted drugs showed promising results in preliminary stages. This study aimed to investigate the association of mutation variants with clinical features and the efficacy of chemotherapy in patients with HER2 mutated advanced NSCLC.ARMS-PCR was used to identify HER2 mutation in patients without common oncogenic alterations. Patients with detailed information were further enrolled for analysis of clinical features and efficacy of first line chemotherapy. Survival data was analyzed by Kaplan-Meier method and compared by log-rank test. Brain metastasis incidence was analyzed and compared by Gray's test.YVMA insertion accounted for the majority (68.4%, 67/98) of HER2 mutation, and associated with significantly higher incidence of baseline extrathoracic metastasis (P=0.009), notably brain metastasis (P=0.004). Among 82 patients those received first line chemotherapy, YVMA insertion remarkably associated with inferior treatment outcomes, namely, a significantly shorter median progression free survival (PFS) and lower objective response rate (ORR) both in total patients (PFS: 5.2 vs. 7.7 m, P=0.038; ORR: 30.9% vs. 51.9%, P=0.09) and pemetrexed subgroup (PFS: 5.2 vs. 6.5 m, P=0.022; ORR: 31.8% vs. 60.0%, P=0.054). Multivariate analysis further established YVMA insertion as prognostic factor of worse PFS both for total patients (HR =1.578, 95% CI, 0.956-2.606) and patients received pemetrexed-based chemotherapy (HR =1.789, 95% CI, 1.013-3.160). In addition, YVMA insertion associated with higher incidence of lifetime brain metastasis (P=0.002) compared by Gray's test, with estimated 12-month brain metastasis incidence as 40.2% compared with 3.6% in the non-YVMA group.YVMA insertion is associated with a higher incidence of brain metastasis, and inferior outcomes to chemotherapy than non-YVMA variants in patients with advanced NSCLC and HER2 kinase domain mutations, which emphasized the unmet need of more potent anti-cancer therapies with high blood-brain barrier (BBB) penetration capacity for patients with YVMA insertion.